Diagnosis of adrenal glands incidentaloma. - O. B. Kutovoy; E. V. Zhmurenko; L. V. Kunyk (Medičnì Perspektivi, 2017)
In this study the results of examination and treatment of 91 patients with adrenal glands incidentaloma were analyzed. According to the results of the morphological study, adenomas were the most common (n=60). Among malignant tumors, ACC was detected in 7 patients, low and undifferentiated cancer – in 3 patients, sarcoma – in 2 patients and metastasis of cancer – in 4 patients. To assess the nature of the tumor, the following criteria were used: size and density according to CT. In 43 patients with neoplasms less than4 cmin 9,3% of cases malignant adrenalomas occurred, at 4-6 cm(n=29) - in 17,2% of cases, more than6 cm(n=19) - in 31,6%. In patients with ACC, 71,4% of tumors exceeded6 cm, 28,5% - were within 4-6 cm, 14,1% - less than4 cm. The frequency of detection of malignant incidentalomas increases in proportion to the growth of tumor size, and with a diameter of more than4 cmit was 27,1%. Adrenal adenomas in 31.6% of cases were from 4 to6 cm, and in 10% - more than6 cm. Thus, the orientation only on the size of tumors did not provide enough convincing grounds for determining its malignant potential. High native density was noted in ACC (33.4±2.8 HU), ganglioneuroma (36.6 НU) and metastases of cancer (43.6±9.0 HU). Low density was found in adenomas (0.4±10.7 HU) and adrenal cysts (6.0±8.2 HU), p<0.05. The most informative method of investigation in adrenal incidentalomas was CT, with sensitivity in adenomas and cancers – 98,3% and 94,4% respectively, specificity – 82,4% and 84,6%.